An observational study examining utilization of prehabilitation and its association with postoperative cardiac rehabilitation participation and risk factors following coronary artery bypass grafting - Rouleau, Codie R.; Chirico, Daniele; Hauer, Trina; Kidd, William; Arena, Ross; Aggarwal, Sandeep G. (International journal of cardiology, 2022)
Growing evidence supports the use of prehabilitation before coronary artery bypass grafting (CABG) to improve surgical outcomes, but its feasibility and impact on risk factor management in real-world clinical settings remain unknown. This observational study examined prehabilitation utilization and its association with postoperative cardiac rehabilitation (CR) participation and cardiovascular risk profile. As standard care in a large Canadian city, eligible patients were referred to prehabilitation upon entering the elective CABG waitlist then were re-referred to CR following surgery. Prehabilitation consisted of medically supervised exercise training and multidisciplinary support with health behavior change until the scheduled surgery. An assessment of cardiorespiratory fitness, blood pressure, body habitus, psychological distress, lipids, glycated hemoglobin, and smoking status was completed during a prehabilitation intake visit then was repeated after surgery prior to starting CR. Among 97 prehabilitation referrals over a 20-month period, only 49% attended an intake visit. Most patients who enrolled (n = 39) also completed (n = 37) prehabilitation. Completion of prehabilitation was significantly associated with higher CR referral (OR = 6.92, 95% CI 1.50–32.00), enrollment (OR = 14.08, 95% CI 5.09–38.94) and attendance [t(62) = 4.48, p < .001], and with improvements in cardiorespiratory fitness, body mass index, and symptoms of depression and anxiety (p < .004). Prehabilitation may improve CR participation and risk factors among individuals undergoing elective CABG, but more work is needed to disseminate this service to eligible patients. •It is important to optimize the waiting time before coronary artery bypass grafting•Prehabilitation may increase cardiac rehabilitation referrals and participation•Patients in prehabilitation show improved risk factor profiles and fitness•More work is needed to support use of prehabilitation by eligible patients